Keputusan Berkunjung Pada Destinasi Wisata : Peran Aksesibilitas, Digital Marketing dan Fasilitas - harjadi, dikdik (LPPM Universitas Buana Perjuangan Karawang, 2024)
The purpose of this study was to determine the effect of accessibility, digitalmarketing, and facilities on the decisions to visit partially and simultaneously. Thetype of research used is quantitative. The method used in this research was descriptiveand verification method. The sample or respondents in this study were adjusted to be100 people (tourists). This makes it easier to process data and for better test results. Incollecting data using documentation and questionnaire techniques. The questionnairescale used was an interval scale of 1 to 10. The calculation to test the proposedhypothesis uses multiple linear regression analysis with the help of the SPSS forwindows version 25 application. The results show: (1) Accessibility, digitalmarketing, and facilities affect the decisions to visit at the Balong Dalem touristattraction. This means that every change in the decisions to visit is influenced byfactors of accessibility, digital marketing, and facilities, (2) Accessibility has a positiveand significant effect on the decisions to visit the Balong Dalem tourist attraction.This means that proper accessibility can increase the decisions to visit, (3) Digitalmarketing has a positive and significant effect on the decisions to visit the BalongDalem tourist attraction. This means that effective digital marketing can improvevisiting decisions, and (4) Facilities have a positive and significant effect on decisionsto visit Balong Dalem tourism objects. This means that complete facilities canimprove visiting decisions